Factors affecting Asiatic caracal occupancy and activity in an arid landscape; vegetation, prey and predator presence are key - Dunford, Carolyn E.; Botha, Alexander; Faure, J. Philip B.; Drouilly, Marine; Stirnemann, Ingrid A.; Mann, Gareth; Serieys, Laurel; Soultan, Alaaeldin; Gallacher, Emma; Mills, David (Global ecology and conservation, 2024)
Predator populations persisting in desert landscapes may be especially vulnerable to habitat fragmentation and changing climates, but many are chronically understudied and at risk of extirpation. The Asiatic subspecies of caracal, Caracal caracal schmitzi, inhabit the mountainous landscapes of the western and southern Arabian Peninsula, but they are thought to be in decline across the region. In Saudi Arabia, a recent extensive study used camera traps and face-to-face questionnaires to survey Arabian leopards and other medium- to large-size mammals, simultaneously generating vast bycatch data on Asiatic caracal presence. We assessed interspecific temporal overlap and identified factors that influence caracal occupancy, and predict their potential distribution across their historical range in Saudi Arabia. From fourteen camera trap surveys, 497 independent captures of caracals were recorded at only the nine south-western sites. Occupancy modelling showed caracals occurred in areas with higher gross primary productivity and elevations, as well as with a higher relative abundance of free-roaming cats and dogs, striped hyaena, and wild prey. Higher abundances of large predators decreased detection of caracals. Caracals displayed a cathemeral activity pattern with peaks of activity around sunrise and sunset, and had a high diel overlap with free-roaming cats and dogs, and wild Arabian wolves. Predictive modelling identified the south western mountains as a stronghold for Asiatic caracals, with low occupancy or recent extirpation in the north and elsewhere, and was highly congruous with predictions from false-positive occupancy modelling from 843 questionnaires. The persistence of caracal populations is likely driven by the increased vegetation and wild prey associated with the southern regions, as well as a more frequent human presence that potentially increases availability of alternative prey, including free-roaming cats. Caracals persisting in dry and desert regions may be particularly vulnerable to climatic changes affecting vegetation and prey abundance, but may have the ability to adapt and benefit from limited human presence if conflict can be avoided. •Caracals in arid landscapes select areas with more vegetation and higher elevations.•Camera traps did not detect caracals in northern historical ranges of Saudi Arabia.•Occupancy models predict caracals populate the southern mountains.•Spatio-temporal overlap with feral cats and dogs indicate anthropogenic interaction.•Consequences of changing climates and human pressures require further research.